The adult growth examination: Validation, analysis, and cross-cultural utility of a compact brief test of individual aging - Morgan, Robert F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A volunteer sample of 5 1 men and 56 women, ages 20 to 70 years, were tested in Nova Scotia, Canada, on the Adult Growth Examination (AGE), a brief compact standardized test of individual aging.